Transforming Indonesia's Zakat in the Digital Era: Opportunities and Challenges - Halili, Halili; Ash Shiddiqi, Hasbi (Al Barakat, 2024)
In the ever-changing digital age, the transition of zakat is becoming more important and urgent. Zakat institutions may boost community involvement in the practice of blessing sharing and achieve increased efficiency in the zakat collection, management, and distribution processes by making prudent use of digital technology. But in order for it to realize its full potential, everyone involved must work together to overcome the obstacles that come with utilizing technology in social and religious contexts. His research employs a qualitative descriptive technique in conjunction with document analysis. The goal of this qualitative descriptive method is to provide an explanation for the events and facts that were noted throughout the Zakat research.Transformation in the Digital Age. Possibilities and Difficulties. The findings of this study indicate that the digital transformation of zakat represents a substantial shift in how zakat is handled and distributed through the use of information and communication technologies. It is important for zakat institutions to be ready for the five opportunities and four obstacles of the digital era's zakat transition. This will ensure that the shift in zakat will benefit both zakat institutions and society at large.